Discrete‐choice experiment to analyse preferences for centralizing specialist cancer surgery services. Issue 5 (7th March 2018) - Vallejo‐Torres, L.; Melnychuk, M.; Vindrola‐Padros, C.; Aitchison, M.; Clarke, C. S.; Fulop, N. J.; Hines, J.; Levermore, C.; Maddineni, S. B.; Perry, C.; Pritchard‐Jones, K.; Ramsay, A. I. G.; et al.
Abstract : Background: Centralizing specialist cancer surgery services aims to reduce variations in quality of care and improve patient outcomes, but increases travel demands on patients and families. This study aimed to evaluate preferences of patients, health professionals and members of the public for the characteristics associated with centralization. Methods: A discrete‐choice experiment was conducted, using paper and electronic surveys. Participants comprised: former and current patients (at any stage of treatment) with prostate, bladder, kidney or oesophagogastric cancer who previously participated in the National Cancer Patient Experience Survey; health professionals with experience of cancer care (11 types including surgeons, nurses and oncologists); and members of the public. Choice scenarios were based on the following attributes: travel time to hospital, risk of serious complications, risk of death, annual number of operations at the centre, access to a specialist multidisciplinary team (MDT) and specialist surgeon cover after surgery. Results: Responses were obtained from 444 individuals (206 patients, 111 health professionals and 127 members of the public). The response rate was 52·8 per cent for the patient sample; it was unknown for the other groups as the survey was distributed via multiple overlapping methods. Preferences were particularly influenced by risk of complications, risk of death and access to a specialist MDT. Participants were willing to travel, on average, 75 min longer in order to reduce their risk of complications by 1 per cent, and over 5 h longer to reduce risk of death by 1 per cent. Findings were similar across groups. Conclusion: Respondents' preferences in this selected sample were consistent with centralization. Abstract : Most favour it